The effect of a back pain campaign on back beliefs, coping strategies and participant activation for nurses in Lusaka, Zambia - Nkhata, Loveness A. (Stellenbosch : Stellenbosch University, 2021)
Thesis (PhD)--Stellenbosch University, 2021.